2013
DOI: 10.3109/09637486.2013.854741
|View full text |Cite
|
Sign up to set email alerts
|

Bone porosity and longevity in early medieval Southern Croatia

Abstract: Porosity of the skull and skeletal remains, especially of the orbital roof, are one of the most frequent pathological findings on ancient human skeletal remains. There are several presumed causes of this condition and anthropologists consider skull porosities as a marker of physical and nutritional stress. A total of 115 graves were discovered at the early-medieval graveyard near Zadar (Croatia) that contained 128 partially preserved skeletons. Average estimated age at death was 37.2 ± 12.6 years for men, 31.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Additionally, the prevalence of cribra orbitalia reported in these modern populations were 24.3% (O'Donnell et al, 2020), 29.6% (Hens et al, 2019), and 33.3% (Rothschild et al, 2021), similar to prevalence reported in many populations across time and around the world (Bečić et al, 2014; Blom et al, 2005; Carlson et al, 1974; Gibbon & Davies, 2020; Juengst et al, 2017; Kalová et al, 2017; Kozak & Krenz‐Niedbała, 2002; Kyle et al, 2018; Lallo et al, 1977; Łubocka, 2000; Nathan et al, 1966; Novak, 2011; Okumura & Eggers, 2005; Redfern et al, 2015; Yaussy et al, 2016; Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Additionally, the prevalence of cribra orbitalia reported in these modern populations were 24.3% (O'Donnell et al, 2020), 29.6% (Hens et al, 2019), and 33.3% (Rothschild et al, 2021), similar to prevalence reported in many populations across time and around the world (Bečić et al, 2014; Blom et al, 2005; Carlson et al, 1974; Gibbon & Davies, 2020; Juengst et al, 2017; Kalová et al, 2017; Kozak & Krenz‐Niedbała, 2002; Kyle et al, 2018; Lallo et al, 1977; Łubocka, 2000; Nathan et al, 1966; Novak, 2011; Okumura & Eggers, 2005; Redfern et al, 2015; Yaussy et al, 2016; Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 73%
“…The prevalence among well‐documented samples from modern times appears similar to prevalence reported in many populations across time and around the world with wide‐ranging diets, lifestyle, disease risks, etc. For example, Gibbon and Davies (2020) document a cribra orbitalia prevalence of 23% in a Holocene Khoesian sample from southern Africa; Juengst et al (2017) documents prevalence of 33% from seven archeological sites in the Copacabana Peninsula at the Titcaca Basin that date from 800 BC – 200 AD; Zhang et al (2016) note a prevalence of 30.3% among a Late Shang population from Anyang, China; Bečić et al (2014) reports a prevalence of 21% among a seventh‐ninth century AD population from the Ostrovica‐Greblje graveyard in Croatia; Novak (2011) documents a prevalence of 35% from a late Medieval Cemetery from Koprivno in Southern Croatia; Blom et al (2005) documents prevalence of 23.1% from coastal populations of Peru dating from 200 BC–1,476 AD; Kozak and Krenz‐Niedbała (2002) report a prevalence of 27.6% in a Kołobrzeg, Poland population dating from the 14th–18th century AD; Łubocka (2000) documents a prevalence of 30.2% from Ostrów Lednicki, an island on the Lednica Lake—Wielkopolska Province, Poland from the 12th–14th centuries AD; Okumura and Eggers (2005) note a prevalence of 29.4% from Sambaqui Jabuticabeira II in Brazil dating from 2,890 ± 55–2,186 ± 60 BP; Lallo et al (1977) document a prevalence of 33.8% among a population from Dickson Mounds and Eiden in Illinois and Ohio (USA) dating from 900–1,350 AD (Dikson Mounds) and 1,490 ± 55 AD (Eiden); and Carlson et al (1974) documents a 21.4% prevalence from a Sudanese Nubia population dating from 350 BC–1,400 AD.…”
Section: Discussionmentioning
confidence: 99%